Kunst und Künstler im Film - Korte, Helmut; Röttgen, Herwarth; Dragica Anderle, Marja; Bauer, Gerd; Hochschule für Bildende Künste, Braunschweig (Hameln : Verlag CW Niemeyer, 1990)
Albers, Josef ; Andreas, Gerhard ; Antes, Horst ; Appelt, Dieter ; Archipenko, Alexander ; Arp, Hans ; Bachem, Bele ; Bacon, Francis ; Bak, Samuel ; Barlach, Ernst ; Baselitz, Georg ; Bauer, Rudolf ; Bauereis, Ulli ; Baum, Otto ; Baumeister, Willi ; Beckmann, Max ; Beuys, Joseph ; Dürer, Albrecht ; etc.
Duits
boek